Study of ink aging: Targeting triethylene glycol in carbon-based black gel ink strokes on paper. (June 2020) - Ni, Yunchang; He, Ning; Lü, Yinni; Zou, Ning; Song, Hui; Li, Hongda; Zhao, Pengcheng
Graphical abstract: Highlights: More ink manufacturers in China use triethylene glycol as a solvent. The evaporation of solvents in ink could be divided into three stages. In the final stage, content of the solvent stop decreasing, producing a flat curve. Estimating the writing age of gel ink in document by content of solvents. Abstract: For the past decades, forensic chemists have made considerable efforts to develop methods capable of dating ballpoint pen ink by monitoring the loss of volatile solvents over time; however, few studies have been reported on carbon-based black gel inks. In China, carbon-based black gel pens are typically used for formal writing and signatures, such as contracts, loan receipts, testaments, and paper tests. Thus, it is imperative to analyze the age of carbon-based black gel inks for questioned document examiners in forensic casework. In this study, by employing the combination of gas chromatography with mass spectrometry (GC–MS) and GC with a flame ionization detector, a useful method for ink dating was proposed according to the dissipation of triethylene glycol from three novel carbon-based black gel inks. The ink aging curves suggested that this approach can distinguish questioned ink samples that are less than or greater than 9 months. This result could help to identify some questioned documents actually written within a month but are passed off as documents written years ago.